BEHAVIORAL EVENT INTERVIEW TRAINING TO IMPROVE COMPETENCY-BASED INTERVIEW SKILLS IN PSYCHOLOGY STUDENT - Marisya Pratiwi; Sayang Ajeng Mardhiyah; Amalia Juniarly; Rachmawati Rachmawati (Conferences of Medical Sciences Dies Natalis, 2021)
One of the undergraduate psychology qualifications (S1) compiled by the Indonesian Psychology Colloquium (AP2TPI, 2019) is being able to conduct observations, interviews, and psychological tests on human behavior phenomena based on the basic concepts of psychological theory with the primary competence understanding the basic principles of psychodiagnostic, being able to apply the principles of observation and interview and able to administer, score and interpret certain psychological tests. Currently, one type of interview technique that is often used in work is the behavior-event interview (BEI). According to McClelland (1998), interviews using competency-based methods have been widely accepted and proven in many studies to test the strengths and weaknesses of the interviewee. Competency-Based Interview Structures are also effective in minimizing subjective assessments that interviewers often do not realize. Therefore, the skills to conduct interviews based on these competencies are considered important for Psychology graduates.